One‐step Electrosynthesis of Poly(1, 5‐diaminonaphthalene)/Graphene Nanocomposite as Platform for Lead Detection in Water. Issue 8 (11th March 2016) - Nguyen, T. Dung; Dang, T. T. Huyen; Thai, Hoang; Nguyen, L. Huy; Tran, D. Lam; Piro, B.; Pham, M. C.
Abstract: A simple electrochemical methodology was described to elaborate a sensor based on poly(1, 5‐diaminonaphthalene)/reduced graphene oxide film onto platinum‐patterned electrodes. The composite electrodes were investigated for Pb 2+ determination using square wave anodic stripping voltammetry. Pb 2+ was first reduced and preconcentrated onto the modified electrodes at −1.0 V, then a positive potential sweep was applied to oxidize Pb 0 . A well‐defined stripping peak appeared at −0.5 V, which was used as analytical signal. The linear detection range was found from 200 ng L −1 to 700 µg L −1 . Interferences with several other metal ions were evaluated. Abstract :